The Effect of Digitalization and Digital Leadership Style Through Organizational Commitment Mediation on Employee Performance at PT. PLN (Persero) UP3 Situbondo - Pakerti, Imbang Satrio; Suswati, Endang; Wijayanti, Tri Cicik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid advancement of digital technology necessitates organizational transformation, compelling state-owned enterprises like PT PLN (Persero) to adopt digital services such as the Yanbung Mobile application. However, its implementation at UP3 Situbondo has yielded inconsistent employee performance outcomes, highlighting a gap in understanding the precise mechanisms at play. This study aims to analyze the effect of digitalization implementation and digital leadership style on employee performance, with organizational commitment as a mediating variable. Using an explanatory quantitative design, data was collected via questionnaires from all 81 Customer Connection Service Officers at PT PLN UP3 Situbondo. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach. The results indicate that digital leadership style has a significant positive direct effect on employee performance. While digitalization implementation significantly increases organizational commitment, it does not directly improve performance. Furthermore, organizational commitment does not significantly affect performance nor mediate the relationships between the independent variables and performance. These findings underscore the paramount importance of competent digital leadership over mere technological adoption in driving performance during digital transformation.